Protest and social conflict in Ayacucho as contentious politics. A preview to the social outburst of December of 2022 - de la Cruz Oriundo, José Eduardo (2023)
Contentious politics regards protests and social mobilization as democratic disputes over the public agenda. Three social protests occurring in the department of Ayacucho before the social outburst of December 7, 2022, are examined under this approach. The three contentious actions and the local reactions to the social outburst are reconstructed through newspaper review. This permitted to identify similar dynamics in the protests and state limitations to channel them into peaceful solutions. Although protests had different agendas, it was possible to identify the recurrence of the Ayacucho People’s Defense Front (FREDEPA). For this reason, the trajectory of this collective actor from its emergence to the present is explored. It is concluded that contentious politics have different results at local and national levels. Locally it amplifies the public agenda, while at the national level polarizes political actors.